Ganciclovir use evaluation in kidney transplantation departments - Maryam Mozaffar; Shahrzad Shahidi; Shirinsadat Badri (Wolters Kluwer Medknow Publications, 2016)
Objective: In this study, we evaluated certain aspects of the usage and administration of one lifesaving, high-cost medication, i.e., Ganciclovir for the prevention and treatment of cytomegalovirus (CMV) infection in transplant patients. Methods: This study was performed from 2013 to 2015 by conducting a medication use evaluation (MUE) program in the kidney transplantation departments of two tertiary care hospitals in Isfahan, Iran. The MUE criteria for the drug were developed by applying drug information references. In every category of data, the number (percent) of cases, in which drug therapy was in accordance with the predetermined criteria, was calculated. Findings: During the study period, 67 cases were observed. The only documented drug interaction was the minor interaction of Ganciclovir with mycophenolate mofetil in 77% of the patients. In all patients, intravenous (IV) infusion was the route of administration, mainly in the peripheral veins. Four patients showed adverse drug reaction, which leads to Ganciclovir discontinuation. Ganciclovir was administered despite contraindication in 34.3% of the patients. Conclusion: In this study, we faced a relatively unacceptable situation, in which Ganciclovir is handled somehow inappropriately. It seems necessary to develop an updated local guideline to approximate the administering pattern of such costly medications to standard protocols.